Sistem Pendukung Keputusan Penentuan Penerima Bantuan Langsung Tunai Menggunakan Metode MOORA - William Charlie Septian Sinaga; Gilbert Johan Martin Sinaga (JIKOMTI : Jurnal Ilmiah Ilmu Komputer dan Teknologi Informasi, 2026)
Direct Cash Assistance (BLT) is a social assistance program aimed at helping low-income communities meet their basic needs. However, the process of determining aid recipients is still often conducted manually, leading to subjectivity and inaccurate targeting. This study aims to implement the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method in a Decision Support System (DSS) to determine the eligibility of BLT recipients objectively and systematically. The study employed five assessment criteria, namely number of dependents, monthly income, employment status, residential status, and ownership of PKH/KKS social assistance. Data were collected through observation, interviews, and documentation of prospective BLT recipients in Gang Nauli, Aek Nauli Village, South Siantar District, Pematangsiantar City. The results indicate that the MOORA method is capable of producing a more objective, transparent, and measurable selection process. Based on the calculation results, alternative A3 obtained the highest preference value and was therefore recommended as the most eligible BLT recipient.